Pemanfaatan Teknologi Finansial dalam Layanan Publik terhadap Efisiensi dan Kualitas Pelayanan Pemerintahan - Kamaluddin, Laode Amijaya (AkMen JURNAL ILMIAH, 2025)
The development of financial technology (Financial Technology/FinTech) has driven significant changes in the delivery of public services, especially in the system of paying taxes, levies, and other government services. This study aims to analyze the influence of the use of FinTech on the efficiency and quality of government services. The research method used is a quantitative approach with survey techniques on government officials and public service users. The data were analyzed using multiple linear regression to test the relationships between variables. The results of the study show that the use of FinTech has a positive and significant effect on the efficiency of public services through increasing transaction speed, financial transparency, and reducing operational costs. In addition, FinTech also affects the quality of government services by increasing accessibility, reliability, and community satisfaction. This study recommends that the government expand the implementation of FinTech to support regional financial digitalization programs and improve public sector performance.